Modifikasi Alat Back And Leg Dynamometer Digital Dilengkapi Parameter Pengklasifikasian Kekuatan Otot Tungkai Dan Otot Punggung Berbasis Arduino - Kusnadi Kusnadi; Hikmah Maya Sari; Aldinor Setiawan; Muhammad Akbar Hariyono (UrbanGreen, 2023)
Back And Leg Dynamometer is a tool used to measure the components of back muscle strength, leg muscles of athletes, patients and workers to evaluate the physical status of performance and task demands. Because it will be beneficial for physical development. The method used in this study is Research and Development (RnD), by developing from previous research. The development carried out is in the addition of measurements for the leg and back muscle modes with a classification system that is carried out automatically with the aim of facilitating the user in measuring the strength of the leg muscles and back muscles. The results of product testing from data in the field can be summarized as follows. Comparison results of the Digital Back and Leg Dynamometer designed with the Analog Back and Leg Dynamometer have a measurement error value of 3%. The voltage generated by the battery is 10.59 Vdc with an error value of 1.59 Vdc and an error accuracy of 0.17%. On Arduino Nano measurements the resulting voltage is 4.75 Vdc with an error value of 0.24 Vdc and an accuracy of errors 4.98%.